Membrane electrode, preparation method thereof and fuel cell

By using a double-layer coating die head to simultaneously coat the catalyst layer and the intermediate dielectric layer in the film electrode preparation, the problems of complex and complicated film electrode preparation and uneven catalyst distribution in the prior art are solved, and an efficient and simplified preparation process is achieved and excellent battery performance.

CN119481179APending Publication Date: 2025-02-18FTXT ENERGY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311011421.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing membrane electrode preparation methods are complicated and complicated and have low operating efficiency, especially during the transfer process of the catalyst layer, which can easily lead to defects in the catalytic layer on the proton exchange membrane and uneven catalyst distribution.

Method used

The catalyst layer slurry and the intermediate dielectric layer slurry are applied to the transfer film simultaneously by using a double-layer coating die. The adhesion between the catalyst layer and the transfer film is reduced through the intermediate dielectric layer, and the catalyst layer is improved. Transfer efficiency.

Benefits of technology

The film electrode preparation process is simplified and efficient, the transfer difficulty is reduced, the uniformity and integrity of the catalyst layer are ensured, and the battery performance of the film electrode is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481179A_ABST
    Figure CN119481179A_ABST
Patent Text Reader

Abstract

The invention provides a membrane electrode, a preparation method thereof and a fuel cell, the preparation method of the membrane electrode adopts a double-layer coating die head to coat catalyst layer slurry and intermediate dielectric layer slurry on the surface of a transfer printing membrane at the same time, and then the transfer printing membrane coated with the catalyst layer slurry and the intermediate dielectric layer slurry is transferred to the surface of a proton exchange membrane. The preparation process of the membrane electrode is simple and efficient, the coating time is saved, and the preparation process can be realized by slightly transforming an existing production line, so that the industrial large-scale production is facilitated. Moreover, the membrane electrode prepared by the invention is excellent in performance, and can improve the water management of the membrane module, so that the membrane module has relatively low mass transfer resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of fuel cells, and in particular to a membrane electrode and a preparation method thereof, and a fuel cell. Background Art

[0002] The membrane electrode is the core component of the proton exchange membrane fuel cell, which consists of a proton exchange membrane, anode and cathode catalyst layers, and cathode and cathode gas diffusion layers. Generally, the preparation methods of the cathode and cathode catalyst layers can be divided into two categories. One is the direct coating method, that is, the catalyst slurry is scraped or sprayed onto the proton exchange membrane; the other is the transfer method, that is, the catalyst slurry is first coated on a special transfer membrane (such as PTFE, PI membrane, etc.), and then transferred to the proton exchange membrane by hot pressing to form a catalyst layer. However, these methods have the following problems: when the direct coating method is used, the catalyst slurry is in direct contact with the proton exchange membrane, which will cause the proton exchange membrane to swell; when the transfer method is used to transfer the catalyst coating, due to the uneven distribution of temperature and pressure, and the catalyst coating contains a binder, there is a certain bonding force with the transfer membrane, resulting in the catalyst coating cannot be completely transferred to the proton exchange membrane, resulting in defects in the catalyst layer on the proton exchange membrane, resulting in uneven distribution of the catalyst.

[0003] In order to solve the above problems, it is necessary to ensure that the catalyst coating on the transfer membrane can be completely transferred to the proton exchange membrane. On the one hand, the existing technology will use high temperature and pressure for transfer, but it will lead to energy waste, and high temperature and high pressure will affect the performance of the catalyst layer; on the other hand, the existing technology will first apply a layer of intermediate medium layer on the surface of the transfer membrane before applying the catalyst slurry, and then apply the catalyst slurry after the intermediate medium layer is dried. Although this method can reduce the adhesion between the catalyst coating and the proton exchange membrane, and reduce the difficulty of transfer, the preparation process is complicated and cumbersome, and the operating efficiency is low.

[0004] Therefore, it is necessary for the present application to provide a new membrane electrode preparation method to solve the problems of the membrane electrode preparation method in the prior art being complicated and cumbersome and having low operating efficiency. Summary of the invention

[0005] The main purpose of the present invention is to provide a membrane electrode and a preparation method thereof, and a fuel cell, so as to solve the problems in the prior art that the membrane electrode preparation method is complicated and cumbersome and has low operating efficiency.

[0006] In order to achieve the above-mentioned object, according to one aspect of the present invention, a method for preparing a membrane electrode is provided, comprising the following steps: providing a catalyst layer slurry, an intermediate medium layer slurry, a first transfer membrane, a second transfer membrane and a proton exchange membrane; wherein the proton exchange membrane has a first outer surface and a second outer surface arranged opposite to each other; using a double-layer coating die head to simultaneously coat a first part of the catalyst layer slurry and a first part of the intermediate medium layer slurry onto a surface of one side of the first transfer membrane, and after drying, obtaining a first transfer substrate on which the first transfer membrane, the first intermediate medium layer and the first catalyst layer are sequentially stacked from bottom to top; coating a second part of the catalyst layer slurry and an optional second part of the intermediate medium layer slurry onto a first transfer substrate; and coating the first transfer membrane, the first intermediate medium layer and the first catalyst layer onto a first transfer substrate. The first transfer substrate is a substrate on which a second transfer film, an optional second intermediate medium layer, and a second catalyst layer are stacked in sequence from bottom to top after drying; the first catalyst layer and the first intermediate medium layer of the first transfer substrate are transferred to the first outer surface of the proton exchange membrane by a first thermal transfer, and the second catalyst layer and the optional second intermediate medium layer of the second transfer substrate are transferred to the second outer surface of the proton exchange membrane by a second thermal transfer to obtain a membrane electrode; wherein the viscosity of the intermediate medium layer slurry at 25°C is 50 to 500 mPa·s, and the viscosity of the catalyst layer slurry at 25°C is 50 to 500 mPa·s.

[0007] Furthermore, in the double-layer coating die head, the ratio of the feed flow rate of the first part of the catalyst layer slurry to the feed flow rate of the first part of the intermediate medium layer slurry is 10:1 to 2:1.

[0008] Furthermore, the ratio of the feed flow rate of the second part of the catalyst layer slurry to the feed flow rate of the optional second part of the intermediate medium layer slurry is 10:1 to 2:1.

[0009] Further, the catalyst layer slurry includes a catalyst, a first polymer binder and a first solvent.

[0010] Furthermore, in the catalyst layer slurry, the weight fraction of the first polymer binder is 20 to 50 wt %, and more preferably 25 to 35 wt %.

[0011] Furthermore, the intermediate medium layer slurry includes a first carbon material, a second polymer binder and a second solvent.

[0012] Furthermore, in the intermediate medium layer slurry, the weight fraction of the second polymer binder is 3 to 80 wt %, and more preferably 5 to 40 wt %.

[0013] Furthermore, the solid content of the catalyst layer slurry is 5 to 60 wt %, and more preferably 6 to 40 wt %.

[0014] Furthermore, the solid content of the intermediate medium layer slurry is 1 to 60 wt %, and more preferably 5 to 30 wt %.

[0015] Furthermore, the active component of the catalyst is selected from one or more of platinum, gold, silver, palladium, cobalt, nickel, titanium, cobalt, copper and oxides thereof.

[0016] Furthermore, the catalyst carrier is selected from one or more of a second carbon material, a metal oxide, a transition metal carbide or a transition metal nitride.

[0017] Furthermore, the loading amount of the active component of the catalyst is 0.1 to 0.4 mg / cm 2 .

[0018] Further, the first carbon material and the second carbon material are each independently selected from one or more of carbon fibers, carbon nanotubes, mesoporous carbon, Ketjen black, graphene, graphite oxide, or reduced graphene oxide.

[0019] Further, the first polymer binder and the second polymer binder are each independently selected from one or more of fluorinated ethylene propylene, polytetrafluoroethylene, polyvinylidene fluoride, perfluorosulfonic acid or partially fluorinated sulfonic acid.

[0020] Furthermore, the first solvent and the second solvent are each independently selected from water and / or alcohol solvents.

[0021] Furthermore, the alcohol solvent is selected from one or more of methanol, ethanol, propanol, butanol, pentanol or hexanol.

[0022] Furthermore, the temperature of the first thermal transfer is 40 to 160° C., and the pressure of the first thermal transfer is 5 to 20 kgf / cm 2 The time of the first thermal transfer is 1 to 60 minutes.

[0023] Furthermore, the temperature of the second thermal transfer is 40 to 160° C., and the pressure of the second thermal transfer is 5 to 20 kgf / cm 2 The time of the second thermal transfer is 1 to 60 minutes.

[0024] Furthermore, the thickness of the first intermediate dielectric layer is 8-15 μm.

[0025] Furthermore, the thickness of the first catalyst layer is 5 to 20 μm.

[0026] Furthermore, the thickness of the second intermediate dielectric layer is 8-15 μm.

[0027] Furthermore, the thickness of the second catalyst layer is 5 to 20 μm.

[0028] In order to achieve the above object, according to one aspect of the present invention, a membrane electrode is provided. The membrane electrode is prepared by the membrane electrode preparation method of the present invention.

[0029] According to another aspect of the present invention, a fuel cell is provided, comprising the membrane electrode of the present invention.

[0030] When the technical solution of the present invention is applied and the conventional transfer method is used to prepare the membrane electrode of the above structure, since the catalyst layer slurry contains a binder and has a certain adhesiveness, part of the catalyst will be bonded to the transfer membrane during the transfer process and cannot be transferred to the surface of the proton exchange membrane. In view of the fact that the existing technical means cannot efficiently and simply solve the problem of difficult transfer in the membrane electrode preparation process, the present invention proposes a method of using a double-layer coating die head to simultaneously coat the catalyst layer slurry and the intermediate medium layer slurry on the surface of the transfer membrane. During coating, the intermediate medium layer slurry contacts the surface of the transfer membrane to form an intermediate medium layer, and the catalyst layer slurry contacts the intermediate medium layer slurry to form a catalyst layer on the surface of the intermediate medium layer. Since the intermediate medium layer is provided between the transfer membrane and the catalyst layer, the intermediate medium layer can reduce the adhesive force between the catalyst layer and the transfer membrane, improve the transfer efficiency of the catalyst layer, and reduce the difficulty of transfer; at the same time, the intermediate medium layer can improve the distribution of water at the interface between the catalyst layer and the gas diffusion layer of the membrane assembly, and liquid water is not easy to gather at the interface, which is beneficial to the mass transfer of gas and improves the battery performance of the membrane electrode.

[0031] In particular, the present invention finds that by controlling the viscosity of the intermediate medium layer slurry at 50 to 500 mPa·s (25°C) and the viscosity of the catalyst layer slurry at 50 to 500 mPa·s (25°C), since the intermediate medium layer slurry and the catalyst layer slurry have high viscosity, there is a large liquid surface tension at the interface of the two layers of slurry, so that a thin layer exists between the intermediate medium layer slurry and the catalyst layer slurry, which hinders the mutual penetration between the intermediate medium layer slurry and the catalyst layer slurry, and effectively avoids the miscibility of the upper catalyst layer slurry and the lower intermediate medium layer slurry, and can efficiently achieve the above-mentioned simultaneous double-layer coating, thereby forming a stable and uniform intermediate medium layer and catalyst layer, and the beneficial effects of the intermediate medium layer and the catalyst layer can be effectively exerted.

[0032] In summary, the membrane electrode preparation process of the present invention is simple and efficient, which saves coating time, and the preparation process can be realized by slightly modifying the existing production line, which is more conducive to industrialized scale-up production. Moreover, the membrane electrode prepared by the present invention has excellent performance, can improve the water management of the membrane assembly, and thus make it have lower mass transfer resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0034] Figure 1A partial process equipment diagram of the membrane electrode preparation method of the present invention is shown;

[0035] Figure 2 The battery power test diagram of the membrane assembly of the membrane electrode assembly prepared in Example 1 of the present invention and Comparative Example 1 is shown.

[0036] Among them, the above-mentioned drawings include the following figure marks: 1. transfer film; 2. intermediate medium layer slurry chamber of the double-layer coating die; 3. catalyst layer slurry chamber of the double-layer coating die. DETAILED DESCRIPTION

[0037] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0038] As described in the background technology section of this application, the membrane electrode preparation method in the prior art is complicated and cumbersome, and has low operating efficiency. In order to solve this problem, this application provides a membrane electrode preparation method, which includes the following steps: providing a catalyst layer slurry, an intermediate medium layer slurry, a first transfer membrane, a second transfer membrane and a proton exchange membrane; and the proton exchange membrane has a first outer surface and a second outer surface arranged oppositely;

[0039] A double-layer coating die is used to simultaneously coat the first part of the catalyst layer slurry and the first part of the intermediate medium layer slurry onto one side surface of the first transfer film, and after drying, a first transfer substrate is obtained on which the first transfer film, the first intermediate medium layer and the first catalyst layer are sequentially stacked from bottom to top;

[0040] Applying the second part of the catalyst layer slurry and the optional second part of the intermediate medium layer slurry onto the second transfer film, and drying to obtain a second transfer substrate stacked with the second transfer film, the optional second intermediate medium layer, and the second catalyst layer in sequence from bottom to top;

[0041] Transferring the first catalyst layer and the first intermediate medium layer of the first transfer substrate to the first outer surface of the proton exchange membrane by a first thermal transfer, and transferring the second catalyst layer and the optional second intermediate medium layer of the second transfer substrate to the second outer surface of the proton exchange membrane by a second thermal transfer to obtain a membrane electrode;

[0042] The viscosity of the intermediate medium layer slurry at 25°C is 50-500 mPa·s; the viscosity of the catalyst layer slurry at 25°C is 50-500 mPa·s.

[0043] When the conventional transfer method is used to prepare the membrane electrode of the above structure, since the catalyst layer slurry contains a binder and has a certain degree of adhesion, part of the catalyst will be adhered to the transfer membrane during the transfer process and cannot be transferred to the surface of the proton exchange membrane. In view of the fact that the existing technical means cannot efficiently and simply solve the problem of difficult transfer in the membrane electrode preparation process, the present invention proposes a method of using a double-layer coating die head to simultaneously apply the catalyst layer slurry and the intermediate medium layer slurry to the surface of the transfer membrane. During coating, the intermediate medium layer slurry contacts the surface of the transfer membrane to form an intermediate medium layer, and the catalyst layer slurry contacts the intermediate medium layer slurry to form a catalyst layer on the surface of the intermediate medium layer. Since the intermediate medium layer is provided between the transfer membrane and the catalyst layer, the intermediate medium layer can reduce the adhesion between the catalyst layer and the transfer membrane, improve the transfer efficiency of the catalyst layer, and reduce the difficulty of transfer; at the same time, the intermediate medium layer can improve the distribution of water at the interface between the catalyst layer and the gas diffusion layer of the membrane assembly, and liquid water is not easy to gather at the interface, which is beneficial to the mass transfer of gas and improves the battery performance of the membrane electrode.

[0044] In particular, the present invention finds that the viscosity of the intermediate medium layer slurry is controlled at 50 to 500 mPa·s (25°C), for example, 50 mPa·s, 100 mPa·s, 200 mPa·s, 300 mPa·s, 400 mPa·s or 500 mPa·s, and the viscosity of the catalyst layer slurry is controlled at 50 to 500 mPa·s (25°C), for example, 50 mPa·s, 100 mPa·s, 200 mPa·s, 300 mPa·s, 400 mPa·s or 500 mPa·s. When the viscosity of the intermediate medium layer slurry and the catalyst layer slurry is not in the range of 50 to 500 mPa·s (25°C), the intermediate medium layer slurry and the catalyst layer slurry cannot be coated simultaneously by a double-layer coating die. This is because when the viscosity of the intermediate medium layer slurry and the catalyst layer slurry is too high, it will affect the coating effect and make it difficult to form a coating; when the viscosity of the intermediate medium layer slurry and the catalyst layer slurry is too low, the intermediate medium layer slurry and the catalyst layer slurry will be miscible, making it difficult to form an independent and uniform intermediate medium layer and catalyst layer. When the viscosity of the intermediate medium layer slurry and the catalyst layer slurry is controlled at 50-500mPa·s (25°C), the intermediate medium layer slurry and the catalyst layer slurry have a higher viscosity, and there is a large liquid surface tension at the interface of the two layers of slurry, so that there is a thin layer between the intermediate medium layer slurry and the catalyst layer slurry, which hinders the mutual penetration between the intermediate medium layer slurry and the catalyst layer slurry, effectively avoiding the miscibility of the catalyst layer slurry of the upper layer and the intermediate medium layer slurry of the lower layer, and can efficiently achieve the above-mentioned simultaneous double-layer coating, thereby forming a stable and uniform intermediate medium layer and catalyst layer, and the beneficial effects of the intermediate medium layer and the catalyst layer can be effectively exerted.

[0045] In summary, the membrane electrode preparation process of the present invention is simple and efficient, which saves coating time, and the preparation process can be realized by slightly modifying the existing production line, which is more conducive to industrialized scale-up production. Moreover, the membrane electrode prepared by the present invention has excellent performance, can improve the water management of the membrane assembly, and thus make it have lower mass transfer resistance.

[0046] In order to obtain a more stable and uniform intermediate medium layer and catalyst layer, the viscosity of the intermediate medium layer slurry at 25°C is 50-200mPa·s, for example, 50mPa·s, 80mPa·s, 100mPa·s, 120mPa·s, 150mPa·s, 180mPa·s or 200mPa·s. The viscosity of the catalyst layer slurry at 25°C is 50-200mPa·s, for example, 50mPa·s, 80mPa·s, 100mPa·s, 120mPa·s, 150mPa·s, 180mPa·s or 200mPa·s. When the viscosity of the intermediate medium layer slurry and the catalyst layer slurry is too high, it will affect the coating effect and reduce the uniformity of the coating; when the viscosity of the intermediate medium layer slurry and the catalyst layer slurry is too low, the intermediate medium layer slurry and the catalyst layer slurry will be miscible.

[0047] In a preferred embodiment, after the above-mentioned simultaneous coating is completed, the slurry is dried within 5 to 10 seconds. In order to further effectively avoid the miscibility of the catalyst layer slurry in the upper layer and the intermediate medium layer slurry in the lower layer, the above-mentioned simultaneous double-layer coating can be more efficiently achieved, thereby forming a more stable and uniform intermediate medium layer and catalyst layer, and the beneficial effects of the intermediate medium layer and the catalyst layer can be effectively exerted. In some optional embodiments, the treatment temperature of the above-mentioned drying is 30 to 100°C, and the treatment time is 2 to 20 minutes.

[0048] In a preferred embodiment, in the double-layer coating die, the ratio of the feed flow rate of the first part of the catalyst layer slurry to the feed flow rate of the first part of the intermediate medium layer slurry is 10:1 to 2:1. For example, it can be 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1 or 2:1. The present invention controls the ratio of the feed flow rate of the first part of the catalyst layer slurry to the feed flow rate of the first part of the intermediate medium layer slurry within the above range, which can achieve a better intermediate medium layer thickness, which is beneficial for subsequent application in batteries to improve the electrical performance of the battery. When the feed flow rate ratio is too high, the first intermediate medium layer will be too thin, thereby increasing the difficulty of transfer; when the feed flow rate ratio is too low, the first intermediate medium layer will be relatively thick, thereby affecting the mass transfer effect of the membrane electrode.

[0049] In a preferred embodiment, the ratio of the feed flow rate of the second part of the catalyst layer slurry to the feed flow rate of the second part of the intermediate medium layer slurry is 10:1 to 2:1. For example, it can be 10:1, 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1 or 2:1. The present invention controls the ratio of the feed flow rate of the second part of the catalyst layer slurry to the feed flow rate of the second part of the intermediate medium layer slurry within the above range, which can achieve a better intermediate medium layer thickness, which is beneficial for subsequent application in batteries to improve the electrical performance of the battery. When the feed flow rate ratio is too high, the second intermediate medium layer will be too thin, which will increase the difficulty of transfer; when the feed flow rate ratio is too low, the second intermediate medium layer will be relatively thick, which will affect the mass transfer effect of the membrane electrode.

[0050] In a preferred embodiment, the catalyst layer slurry includes a catalyst, a first polymer binder and a first solvent; preferably, in the catalyst layer slurry, the weight fraction of the first polymer binder is 20 to 50 wt%. By controlling the weight fraction of the first polymer binder within the above range, a suitable viscosity can be obtained, a better coating effect can be obtained, and the formed catalyst layer is more uniform and more stable. More preferably, it is 25 to 35 wt%.

[0051] In a preferred embodiment, the intermediate medium layer slurry includes a first carbon material, a second polymer binder and a second solvent; preferably, in the intermediate medium layer slurry, the weight fraction of the second polymer binder is 3 to 80wt%. When the weight fraction of the first polymer binder is controlled at 3 to 80wt%, the intermediate medium layer slurry can have a suitable viscosity and obtain a better coating effect. When the weight fraction of the second polymer binder is too high, the viscosity of the intermediate medium layer slurry will be too high, affecting the coating effect and even clogging the coating head; when the weight fraction of the second polymer binder is too low, the viscosity of the intermediate medium layer slurry will be too low, the fluidity will be enhanced, and it will be unfavorable for the coating of the upper catalyst slurry. It is further preferably 5 to 40wt%; more preferably 15 to 30wt%.

[0052] In a preferred embodiment, the solid content of the catalyst layer slurry is 5 to 60wt%. For example, it can be 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%. When the solid content of the catalyst layer slurry of the present invention is controlled at 5 to 60wt%, the catalyst layer slurry can have suitable viscosity, and the solid particles have better dispersibility in the slurry to obtain a better coating effect, thereby forming a more uniform and stable catalyst layer. More preferably, it is 6 to 40wt%.

[0053] In a preferred embodiment, the solid content of the intermediate dielectric layer slurry is 1-60wt%. For example, it can be 1wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%. When the solid content of the intermediate dielectric layer slurry of the present invention is controlled at 1-60wt%, the intermediate dielectric layer slurry can have suitable viscosity, and the solid particles have better dispersibility in the slurry to obtain a better coating effect, thereby forming a more uniform and stable intermediate dielectric layer. More preferably, it is 5-30wt%.

[0054] In a preferred embodiment, the active component of the catalyst is selected from one or more of platinum, gold, silver, palladium, cobalt, nickel, titanium, cobalt, copper and oxides thereof.

[0055] In order to obtain a catalyst layer with better comprehensive performance and increase the stability of the catalyst active components, the catalyst carrier is preferably selected from one or more of a second carbon material, a metal oxide, a transition metal carbide or a transition metal nitride.

[0056] In some optional embodiments, the metal oxide is selected from one or more of titanium oxide, molybdenum oxide, manganese oxide, tantalum oxide, niobium oxide or vanadium oxide; the transition metal carbide is selected from one or more of molybdenum carbide, manganese carbide, tantalum carbide, niobium carbide or vanadium carbide; the transition metal nitride is selected from one or more of molybdenum nitride, manganese nitride, tantalum nitride, niobium nitride or vanadium nitride.

[0057] The present application does not specifically limit the first carbon material and the second carbon material, and any carbon material commonly used by those skilled in the art may be selected. Of course, in order to further improve the comprehensive performance of the product, in a preferred embodiment, the first carbon material and the second carbon material are each independently selected from one or more of carbon fiber, carbon nanotube, mesoporous carbon, Ketjen black, graphene, graphite oxide or reduced graphene oxide.

[0058] In a preferred embodiment, the loading amount of the active component of the catalyst is 0.1 to 0.4 mg / cm 2 The catalyst carrier of the present invention has a high loading amount, which will increase the preparation cost, and the catalyst carrier with a loading amount exceeding 0.4 mg / cm 2 The catalytic performance was not significantly improved when the loading amount of the active component of the catalyst was controlled at 0.1-0.4 mg / cm 2 When the catalyst is prepared, both better catalytic performance and lower preparation cost can be taken into account.

[0059] In a preferred embodiment, the first polymer binder and the second polymer binder are each independently selected from one or more of fluorinated ethylene propylene, polytetrafluoroethylene, polyvinylidene fluoride, perfluorosulfonic acid or partially fluorinated sulfonic acid. Partially fluorinated sulfonic acid is purchased from Ballard. When the first polymer binder and the second polymer binder of the present invention are selected from the above types, they have better hydrophilicity or hydrophobicity, and can better adjust the hydrophilicity and hydrophobicity of the coating according to the hydrophilicity and hydrophobicity requirements of the product, thereby improving the mass transfer effect and water management of the membrane electrode.

[0060] In order to obtain intermediate medium layer slurry and catalyst layer slurry with better dispersibility, the first solvent and the second solvent are each independently selected from water and / or alcohol solvents. Preferably, the alcohol solvent is selected from one or more of methanol, ethanol, propanol, butanol, pentanol or hexanol.

[0061] In a preferred embodiment, the first transfer film and the second transfer film are independently selected from one or more of a polytetrafluoroethylene film, a polyimide film or an expanded polytetrafluoroethylene film.

[0062] In order to obtain a higher transfer efficiency of the first catalytic layer and the second catalytic layer, it is preferred that the temperature of the first thermal transfer is 40 to 160°C, and the pressure of the first thermal transfer is 5 to 20 kgf / cm 2 The time of the first thermal transfer is 1 to 60 minutes; preferably, the temperature of the second thermal transfer is 40 to 160°C, and the pressure of the second thermal transfer is 5 to 20 kgf / cm 2 The time of the second thermal transfer is 1 to 60 minutes.

[0063] In some preferred embodiments, the thickness of the first intermediate medium layer is preferably 8 to 15 μm; the thickness of the first catalyst layer is preferably 5 to 20 μm. When the thickness of the first intermediate medium layer is controlled at 8 to 15 μm, the first catalyst layer can be effectively supported, the transfer efficiency of the first catalyst layer can be improved, and the first catalyst layer can be completely transferred to the surface of the proton exchange membrane. At the same time, the membrane electrode also has a better mass transfer effect. When the thickness of the first catalyst layer is controlled at 5 to 20 μm, the amount of precious metals used can be reduced while ensuring the active component loading of the catalyst.

[0064] In some preferred embodiments, the thickness of the second intermediate medium layer is preferably 8 to 15 μm; the thickness of the second catalyst layer is preferably 5 to 20 μm. When the thickness of the second intermediate medium layer is controlled at 8 to 15 μm, the second catalyst layer can be effectively supported, the transfer efficiency of the second catalyst layer can be improved, and the second catalyst layer can be completely transferred to the surface of the proton exchange membrane. At the same time, the membrane electrode also has a better mass transfer effect. When the thickness of the first catalyst layer is controlled at 5 to 20 μm, the amount of precious metals used can be reduced while ensuring the active component loading of the catalyst.

[0065] The present application also provides a membrane electrode, which is prepared using the membrane electrode preparation method of the present invention.

[0066] Based on the above reasons, the membrane electrode obtained by the membrane electrode preparation method of the present invention has lower mass transfer resistance and good water management ability.

[0067] The present application also provides a fuel cell, comprising a membrane electrode obtained by the membrane electrode preparation method of the present invention.

[0068] Based on the above reasons, when the membrane electrode prepared by the present invention is applied to a fuel cell, the fuel cell has excellent battery performance.

[0069] Example 1

[0070] Providing a catalyst layer slurry: the catalyst layer slurry is a mixture of platinum, graphene, perfluorosulfonic acid and water, and the viscosity is 200mPa·s at 25°C; wherein the weight fraction of perfluorosulfonic acid in the catalyst layer slurry is 40wt%, the solid content of the catalyst layer slurry is 9wt%, and the loading amount of platinum, the active component of the catalyst, is 0.27mg / cm 2 .

[0071] Providing an intermediate dielectric layer slurry: the intermediate dielectric layer slurry is a mixture of graphene, perfluorosulfonic acid and water, and has a viscosity of 150 mPa·s at 25° C.; wherein the weight fraction of perfluorosulfonic acid in the intermediate dielectric layer slurry is 30wt%, and the solid content of the intermediate dielectric layer slurry is 9wt%.

[0072] like Figure 1 As shown, a portion of the intermediate medium layer slurry is placed in the intermediate medium layer slurry chamber 2 of the double-layer coating die head, and a portion of the catalyst layer slurry is placed in the catalyst layer slurry chamber 3 of the double-layer coating die head; then the intermediate medium layer slurry and the catalyst layer slurry in the intermediate medium layer slurry chamber 2 of the double-layer coating die head and the catalyst layer slurry chamber 3 of the double-layer coating die head are simultaneously coated on one side surface of the transfer film 1 (polytetrafluoroethylene film); in the double-layer coating die head, the feed flow rate of the catalyst layer slurry is 5:1. After the coating is completed, the slurry is dried within 5 to 10 seconds (the temperature is 60°C and the time is 10 minutes) to obtain a first transfer substrate of a polytetrafluoroethylene film, a first intermediate medium layer and a first catalyst layer stacked in sequence from bottom to top;

[0073] A double-layer coating die is used to simultaneously coat the other part of the catalyst layer slurry and the other part of the intermediate medium layer slurry onto one side surface of the polytetrafluoroethylene membrane (in the double-layer coating die, the ratio of the feed flow rate of the catalyst layer slurry to the feed flow rate of the intermediate medium layer slurry is 5:1), and after drying, a second transfer substrate is obtained in which the polytetrafluoroethylene membrane, the second intermediate medium layer and the second catalyst layer are stacked in sequence from bottom to top;

[0074] The first transfer substrate was subjected to a first thermal transfer (the thermal transfer temperature was 150° C. and the thermal transfer pressure was 15 kgf / cm 2 , the thermal transfer time is 1min) to the first outer surface of the proton exchange membrane; the second transfer substrate is subjected to a second thermal transfer (the thermal transfer temperature is 150°C, the thermal transfer pressure is 15kgf / cm 2 , thermal transfer time is 1 min) to the second outer surface of the proton exchange membrane to obtain a membrane electrode.

[0075] The thickness of the first catalyst layer and the second catalyst layer of the membrane electrode is 15 μm, and the thickness of the first intermediate medium layer and the second intermediate medium layer is 10 μm.

[0076] Comparative Example 1

[0077] The same catalyst layer slurry as in Example 1 was provided.

[0078] Directly coating a portion of the catalyst layer slurry onto one side of the polytetrafluoroethylene membrane, and drying to obtain a first transfer substrate having a polytetrafluoroethylene membrane and a first catalyst layer stacked in sequence from bottom to top;

[0079] The other part of the catalyst layer slurry is directly coated on one side of the polytetrafluoroethylene membrane, and after drying, a second transfer substrate is obtained in which the polytetrafluoroethylene membrane and the second catalyst layer are sequentially stacked from bottom to top;

[0080] The first transfer substrate was subjected to a first thermal transfer (the thermal transfer temperature was 150° C. and the thermal transfer pressure was 15 kgf / cm 2 , the thermal transfer time is 1min) to the first outer surface of the proton exchange membrane; the second transfer substrate is subjected to a second thermal transfer (the thermal transfer temperature is 150°C, the thermal transfer pressure is 15kgf / cm 2 , thermal transfer time is 1 min) to the second outer surface of the proton exchange membrane to obtain a membrane electrode.

[0081] Performance Testing

[0082] The membrane electrode of the above-mentioned embodiment 1 and comparative example 1 was combined with a gas diffusion layer to form a membrane assembly, and the membrane electrode assembly was subjected to polarization test on a test bench. The test conditions were temperature 80°C, cathode and anode pressure 250 / 260KPa, cathode and anode humidity 40 / 50%, and cathode and anode stoichiometry ratio 1.7 / 1.5. The test results are shown in Figure 2 .

[0083] from Figure 2 It can be seen that the battery power of Example 1 using the membrane electrode preparation method of the present invention is higher than the power of the battery of Comparative Example 1. This is because the present invention uses a double-layer coating die to simultaneously coat the catalyst layer and the intermediate medium layer, and an intermediate medium layer is arranged between the transfer membrane and the catalyst layer. The intermediate medium layer can reduce the bonding force between the catalyst layer and the transfer membrane, improve the transfer efficiency of the catalyst layer, and reduce the difficulty of transfer. The catalyst layer can be completely transferred to the surface of the proton exchange membrane, so that the performance of the catalyst layer is fully exerted, thereby improving the power of the battery; and the intermediate medium layer can improve the distribution of water at the interface between the catalyst layer and the gas diffusion layer of the membrane assembly, and liquid water is not easy to gather at the interface, which is beneficial to the mass transfer of gas and further improves the power of the battery.

[0084] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a membrane electrode, characterized in that: The following steps are involved: Providing a catalyst layer slurry, an intermediate medium layer slurry, a first transfer membrane, a second transfer membrane and a proton exchange membrane; wherein the proton exchange membrane has a first outer surface and a second outer surface that are arranged opposite to each other; The first part of the catalyst layer slurry and the first part of the intermediate medium layer slurry are simultaneously coated on one side of the first transfer film by using a double-layer coating die head, and after drying, a first transfer substrate is obtained on which the first transfer film, the first intermediate medium layer and the first catalyst layer are sequentially stacked from bottom to top; Applying the second part of the catalyst layer slurry and the optional second part of the intermediate medium layer slurry onto the second transfer film, and drying to obtain a second transfer substrate stacked with the second transfer film, the optional second intermediate medium layer, and the second catalyst layer in sequence from bottom to top; Transferring the first catalyst layer and the first intermediate medium layer of the first transfer substrate to the first outer surface of the proton exchange membrane by a first thermal transfer, and transferring the second catalyst layer and the optional second intermediate medium layer of the second transfer substrate to the second outer surface of the proton exchange membrane by a second thermal transfer, to obtain the membrane electrode; Wherein, the viscosity of the intermediate medium layer slurry at 25°C is 50-500 mPa·s, and the viscosity of the catalyst layer slurry at 25°C is 50-500 mPa·s.

2. The method for preparing a membrane electrode according to claim 1, characterized in that: In the double-layer coating die head, the ratio of the feed flow rate of the catalyst layer slurry in the first part to the feed flow rate of the intermediate medium layer slurry in the first part is 10:1 to 2:1; Preferably, the ratio of the feed flow rate of the catalyst layer slurry in the second part to the feed flow rate of the intermediate medium layer slurry in the optional second part is 10:1 to 2:

1.

3. The method for preparing a membrane electrode according to claim 1 or 2, characterized in that: The catalyst layer slurry includes a catalyst, a first polymer binder and a first solvent; Further preferably, in the catalyst layer slurry, the weight fraction of the first polymer binder is 20 to 50 wt%, and further preferably 25 to 35 wt%; Preferably, the intermediate medium layer slurry comprises a first carbon material, a second polymer binder and a second solvent; More preferably, in the intermediate medium layer slurry, the weight fraction of the second polymer binder is 3 to 80 wt %, and more preferably 5 to 40 wt %.

4. The method for preparing a membrane electrode according to claim 3, characterized in that: The solid content of the catalyst layer slurry is 5 to 60 wt%, more preferably 6 to 40 wt%; Preferably, the solid content of the intermediate medium layer slurry is 1 to 60 wt %, more preferably 5 to 30 wt %.

5. The method for preparing a membrane electrode according to claim 3 or 4, characterized in that: The active component of the catalyst is selected from one or more of platinum, gold, silver, palladium, cobalt, nickel, titanium, cobalt, copper and oxides thereof; Preferably, the support of the catalyst is selected from one or more of a second carbon material, a metal oxide, a transition metal carbide or a transition metal nitride; Preferably, the loading amount of the active component of the catalyst is 0.1 to 0.4 mg / cm 2 ; Preferably, the first carbon material and the second carbon material are each independently selected from one or more of carbon fibers, carbon nanotubes, mesoporous carbon, Ketjen black, graphene, graphite oxide or reduced graphene oxide.

6. The method for preparing a membrane electrode according to claim 3, characterized in that: The first polymer binder and the second polymer binder are each independently selected from one or more of fluorinated ethylene propylene, polytetrafluoroethylene, polyvinylidene fluoride, perfluorosulfonic acid or partially fluorinated sulfonic acid; Preferably, the first solvent and the second solvent are each independently selected from water and / or alcohol solvents; Further preferably, the alcohol solvent is selected from one or more of methanol, ethanol, propanol, butanol, pentanol or hexanol.

7. The method for preparing a membrane electrode according to any one of claims 1 to 6, characterized in that: The temperature of the first thermal transfer is 40 to 160° C., and the pressure of the first thermal transfer is 5 to 20 kgf / cm 2 , the first thermal transfer time is 1 to 60 minutes; Preferably, the temperature of the second thermal transfer is 40-160°C, and the pressure of the second thermal transfer is 5-20 kgf / cm 2 , the time of the second thermal transfer is 1 to 60 minutes.

8. The method for preparing a membrane electrode according to any one of claims 1 to 7, characterized in that: The thickness of the first intermediate dielectric layer is 8 to 15 μm; Preferably, the thickness of the first catalyst layer is 5 to 20 μm; Preferably, the thickness of the second intermediate dielectric layer is 8 to 15 μm; Preferably, the second catalyst layer has a thickness of 5 to 20 μm.

9. A membrane electrode, characterized in that: The membrane electrode is prepared by the membrane electrode preparation method according to any one of claims 1 to 8.

10. A fuel cell, characterized in that: The fuel cell comprises the membrane electrode according to claim 9.

Citation Information

Cited By

  • Anode catalyst layer, preparation method thereof and membrane electrode

    CN120844129A